Analisis Persiapan Guru Dalam Perencanaan Pembelajaran - Safran Safran; Paisal Rahman Hutapea; Anggun Dela Puspita; Nurintan Maghfirah; Shadrina Azzahra (Universitas Palan, 2024)
This article will introduce what teachers need to do to prepare for the learning process. Teachers need to prepare something for the learning process. Things that teachers must prepare (creating a comfortable school environment with appropriate methods, developing teacher professionalism, etc.)